PENGARUH PENGGANTIAN TEPUNG IKAN DENGAN LIMBAH WINE ANGGUR TERFERMENTASI TERHADAP PERFORMANS BROILER - WIRA SUSANA I W.; I M. NURIYASA; N. W. SITI (Fakultas Peternakan Universitas Udayana, 2018)
The research aims at analyzing the effect of fish flour replacement with fermented wine waste in rations to thebroiler performances. It was conducted using a Complete Random Design with 5 treatments and 5 replications..The treatments were ration using 10% of fish flour and without (0%) waste of fermented wine (R0); ration using7.5% of fish flour, and 2.5% waste of fermented wine (R1); ration using 5% of fish flour, and 5% waste of fermentedwine (R2); ration using 2.5% of fish flour and 7.5% waste of fermented wine (R3); ration without (0%) fish flourand 10% waste of fermented wine (R4). Variables observed were performance including feed consumption, bodyweight gain, final body weight and feed conversion. The results showed that final weight , weight gain and feedconsumption was highest on R1 treatment compared to R0, R2, R3, and R4 (P <0.05). In contrast, the value of feedconversion was similar (P> 0.05). It can be concluded that the highest ferformance on broiler fed ration using 7.5%of fish flour, and 2.5% waste of fermented wine.